Effectiveness of Sensory Integration Therapy in Children with ADHD (Attention Deficit/Hyperactivity Disorder) - Rahmania, Tia; Wulandari, Devi (ANIMA Indonesian Psychological Journal, 2010)
ADHD is one of the most frequently diagnosed disorders in childhood. Ratings by teachers and parents indicated that seven to 10 % of American children meet DSM-IV-TR criteria for the disorder, making ADHD the most common childhood disorder. It showed us that it is very important to look for the best intervention therapy for ADHD. A therapy that parents can choose is sensory integration therapy. The present study investigates the effectiveness of sensory integration therapy for children with ADHD. Data was obtained from children who followed sensory therapy for two months up to seven months. A qualitative method was conducted, specifically using interview and observation. Results reveal that subjects show improvement in three important aspects that are the core to ADHD symptoms (inattention, hyperactivity and impulsivity). It can be concluded that sensory integration therapy was effective in improving children with ADHD. ADHD menjadi salah satu masalah yang kerap didiagnosis pada anak-anak. Peringkat yang dilakukan oleh guru dan orangtua mengindikasikan bahwa tujuh sampai sampai 10% anak di Amerika memenuhi kriteria yang disebutkan dalam DSM-IV-TR. Hal ini menjadikan ADHD kelainan paling umum yang terjadi pada masa anak-anak, sehingga menemukan penanganan dan terapi terbaik bagi anak-anak penyandang sangat mendesak. Salah satu adalah terapi sensori integrasi. Penelitian ini bertujuan menyelidiki keefektifan terapi sensori integrasi untuk penyandang ADHD. Data diperoleh dari anak-anak yang telah mengikuti terapi sensori integrasi selama dua hingga tujuh bulan. Metode yang dipakai adalah metode kualitatif, khususnya cara wawancara dan observasi. Hasil penelitian menunjukkan adanya perbaikan dalam tiga aspek penting yang merupakan masalah utama dari simtom-simtom ADHD (kurang mampu memperhatikan, hiperaktivitas dan impulsivitas). Dapat disimpulkan bahwa terapi integrasi sensori efektif untuk menangani simtom-simtom pada anak-anak dengan masalah ADHD.